(untitled) (The Pakistan Development Review, 2010)
Different safety measures adopted by governments across the globe require the estimates of willingness to pay of the people to swap wealth for a reduction in the probability of death and injury. The approximation of these trade-offs are employed in assessing the cost-benefit analysis of environmental issues, public safety measures on highways and roads, medical treatments, and many other areas. Economists term a trade-off between money and fatality risks as the Value of a Statistical Life (VSL). The Value of Statistical Life and Limb is generally predicted using one of the three main approaches. The first is by the compensating wage differentials that workers must be paid to take riskier jobs [Viscusi and Aldy (2003)]. The second approach examines other behaviours where people weigh costs against risks [Blomquist (2004)] and the third is through contingent valuation surveys where respondents report their willingness to pay (WTP) to obtain a specified reduction in mortality risks. The VSL is then obtained by dividing the WTP by the risk reduction being valued [Alberini (2005)].